Rancang Bangun Kontrol dan Monitoring Suhu Pada Mesin Diesel Menggunakan Mobile - Mohammad Hasan Fuadi (Jurnal Jaringan Telekomunikasi, 2020)
Diesel engines is generally used for industrial and agricultural machines. Few people care about the engine temperature so it is forced to reach temperature of 100oC, which causes overheating of the diesel engine and has an impact on the performance itself. This also uses a hopper cooling system which is certainly not effective, because it's necessary to see that the water in the reservoir is still or not, also not equipped with an engine temperature display so it's difficult to ascertain the temperature inside. This study aims to monitor and control the temperature of cooling water. Operation of temperature control uses a telecontrol system that is connected to network (Internet of Things) so diesel temperature control can be done remotely. Monitoring of temperature and water level in the reserve tank using Web Mobile. In addition, there is a temperature sensor that is used to measure the temperature of the cooling water so that users can monitor the temperature of the diesel engine on Web Mobile. The test results obtained, the temperature sensor has an average temperature reading error of 0.031004%. Diesel engines with controlled solenoid valve cooling systems can produce ideal temperatures compared to when the solenoid valve is open (using the radiator continuously) or when the solenoid valve is Closed (without using a radiator). When the solenoid is controlled the engine temperature can be ideal because the solenoid valve opening and closing system has the lowest temperature of 56.34oC and the highest temperature of only 80.85oC.